Dust & soul of Fitzgerald's Omar Khayyam - Sundaresa Iyer, K. V. (Kalakshetra Publications, 1977)
On the English verse transcreation of Omar Khayyam's Rubāiyāt by Edward Fitzgerald, 1809-1883; includes text interspersed with exegesis and commentary.